2017
DOI: 10.1038/s41598-017-08808-y
|View full text |Cite
|
Sign up to set email alerts
|

Determining the geographical origin of common buckwheat from China by multivariate analysis based on mineral elements, amino acids and vitamins

Abstract: This study aimed to establish a method for distinguishing the geographical origin of common buckwheat from Inner Mongolia, Shanxi and Shaanxi Provinces in China. Three chemical families including mineral elements, vitamins and amino acids of 48 samples from different geographical origins were analyzed by principal component analysis (PCA), cluster analysis (CA) and linear discriminate analysis (LDA) for this purpose. LDA clearly discriminated the geographical origin of common buckwheat samples grown in three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…However, at the saturation point, the net water absorption rate of the tartary buckwheat samples (approximately 125%) was significantly ( P < 0.0001) higher compared to that of the common buckwheat samples (approximately 60%). Such notable differences may be explained by their distinct osmolarities generated by their diverse macro‐ (proteins, starches, and fibers) and micro‐ (vitamins and minerals) nutrient contents …”
Section: Resultsmentioning
confidence: 83%
“…However, at the saturation point, the net water absorption rate of the tartary buckwheat samples (approximately 125%) was significantly ( P < 0.0001) higher compared to that of the common buckwheat samples (approximately 60%). Such notable differences may be explained by their distinct osmolarities generated by their diverse macro‐ (proteins, starches, and fibers) and micro‐ (vitamins and minerals) nutrient contents …”
Section: Resultsmentioning
confidence: 83%
“…Amaranth contains the highest amount of minerals followed by quinoa and buckwheat Zhang and Xu, 2017). In a comparative study, it was observed that tartary buckwheat seeds contained higher levels of minerals than common buckwheat (Bonafaccia et al, 2003).…”
Section: Minerals and Vitaminsmentioning
confidence: 99%
“…So far, graphite furnace atomic absorption spectrometry (GFAAS), flame atomic absorption spectrometry (FAAS), inductively coupled plasma optical emission spectrometry (ICP-OES), inductively couple plasma mass spectrometry (ICP-MS) and high resolution mass spectrometry (HRMS) have been applied to determine the content of trace elements or stable isotope ratio, combined with supervised pattern recognition techniques, such as linear discriminant analysis (LDA), k-nearest neighbours ( k -NN), support vector machine (SVM) and artificial neural network (ANN), providing a useful tool for the differentiation of the geographical origin of products. From the reported studies in the literature, this strategy has been successfully applied to agricultural products (cereal 6 , wheat 7 , 8 , buckwheat 9 , rice 10 , 11 , onion 12 , 13 , sesame seed 14 , potato 15 , honey 16 , pumpkin seed oil 17 , chili pepper 18 , cocoa bean 19 , seafood (prawn 20 , fish 21 ), fruit (date palm 22 , Sechium edule fruit 23 , lemon juice 24 , meat (wild rabbit meat 25 , tea 26 , pork 27 ) and wine 28 .…”
Section: Introductionmentioning
confidence: 99%